From Guardian of the Constitution to Interpreter of Social Justice: An Analysis of the Post-Reform Role of the Constitutional Court and the Threat of Its Politicization - Michael Chandra O; Ehri Ehri; Winson Winson (International Journal Labs, 2025)
The birth of the post-reform Constitutional Court (MK) is often narrowly interpreted by the public as that of